Design of a randomised, placebo-controlled clinical trial of nintedanib in patients with systemic sclerosis-associated interstitial lung disease (SENSCIS(TM)) - Distler, Oliver; Brown, Kevin K; Distler, Jörg; Assassi, Shervin; Maher, Toby M; Cottin, Vincent; Varga, John; Coeck, Carl; Gahlemann, Martina; Sauter, Wiebke; Schmidt, Hendrik; Highland, Kristin B (Clinical and Experimental Rheumatology, 2017)
Nintedanib is a tyrosine kinase inhibitor approved for the treatment of idiopathic pulmonary fibrosis (IPF). The pathological pathways involved in fibrogenesis in IPF and interstitial lung disease associated with systemic sclerosis (SSc-ILD) show commonalities; both involve fibroblast activation, myofibroblast accumulation and deposition of extracellular matrix. The SENSCIS(TM) trial is a randomised, placebo-controlled Phase III trial that will evaluate the efficacy and safety of nintedanib in patients with SSc-ILD (NCT02597933).Approximately 520 patients with SSc (based on 2013 American College of Rheumatology/European League Against Rheumatism criteria) and ILD (>=10% fibrosis of the lungs, confirmed by central assessment of chest high resolution computed tomography), forced vital capacity (FVC) >=40% predicted and diffusing capacity for carbon monoxide of 30-89% predicted will be enrolled. Patients will be randomised (1:1) to nintedanib 150 mg twice daily or placebo, stratified by the presence of anti-topoisomerase I antibody. To reflect real-world management, patients receiving prednisone (<=10 mg/day) and/or a stable dose of mycophenolate or methotrexate, will be eligible. The primary endpoint is the annual rate of decline in FVC (mL/ year) assessed over 52 weeks. Patients will remain on blinded study treatment until the last patient completes 52 weeks of treatment or for a maximum of 100 weeks of treatment. Key secondary endpoints are absolute changes from baseline in modified Rodnan skin score and St George's Respiratory Questionnaire at week 52.Recruitment for the trial began in November 2015.This trial will assess the efficacy and safety of nintedanib in patients with SSc-ILD.
EVALuna2:13440